Serapan Karbon Hutan Mangrove di Bagek Kembar Kecamatan Sekotong Kabupaten Lombok Barat - Baiq Farista; Arben Virgota (Bioscientist : Jurnal Ilmiah Biologi, 2021)
The environmental services of mangrove forests as carbon sinks are one of the indirect benefits of the mangrove ecosystem. The absorption of carbon is carried out by mangrove vegetation through the process of photosynthesis. In this study, mangrove environmental services as carbon sinks are based on the ability to absorb CO2 expressed in carbon units (tC, tCO2), and the economic value of carbon storage in monetary units (Rp). This research was conducted in the Bagek Kembar Mangrove Ecotourism Area, Sekotong District, West Lombok Regency. The method used to take samples is stratified random sampling, where the placement of the plots is determined randomly. The observation plots for each type of growth are arranged in stages with different sizes. The plots are 10 m x 10 m for trees, 5 x 5 m for seedlings, and 2 x 2 m for seedlings. Trees are mangroves with trunk diameter > 4 cm, tillers have a stem diameter of 4 cm and, a height of > 1 m, and seedlings are mangroves with a height of < 1 m. This research shows that the mangrove vegetation in the research location has absorbed 6,437.80 tonnes of CO2eq, and a monetary value of Rp. 482.834.700 (four hundred eighty-two million eight hundred and thirty-four thousand and seven hundred rupiahs).